(E)-1-(3-(3-Hydroxy-4-Methoxyphenyl)-1-(3,4,5-Trimethoxyphenyl)allyl)-1H-1,2,4-Triazole and Related Compounds: Their Synthesis and Biological Evaluation as Novel Antimitotic Agents Targeting Breast Cancer - Gloria Ana; Azizah M. Malebari; Sara Noorani; Darren Fayne; Niamh M. O’Boyle; Daniela M. Zisterer; Elisangela Flavia Pimentel; Denise Coutinho Endringer; Mary J. Meegan (Pharmaceuticals)
Background/Objectives: The synthesis of (E)-1-(1,3-diphenylallyl)-1H-1,2,4-triazoles and related compounds as anti-mitotic agents with activity in breast cancer was investigated. These compounds were designed as hybrids of the microtubule-targeting chalcones, indanones, and the aromatase inhibitor letrozole. Methods: A panel of 29 compounds was synthesized and examined by a preliminary screening in estrogen receptor (ER) and progesterone receptor (PR)-positive MCF-7 breast cancer cells together with cell cycle analysis and tubulin polymerization inhibition. Results: (E)-5-(3-(1H-1,2,4-triazol-1-yl)-3-(3,4,5-trimethoxyphenyl)prop-1-en-1-yl)-2-methoxyphenol 22b was identified as a potent antiproliferative compound with an IC50 value of 0.39 mM in MCF-7 breast cancer cells, 0.77 mM in triple-negative MDA-MB-231 breast cancer cells, and 0.37 mM in leukemia HL-60 cells. In addition, compound 22b demonstrated potent activity in the sub-micromolar range against the NCI 60 cancer cell line panel including prostate, melanoma, colon, leukemia, and non-small cell lung cancers. G2/M phase cell cycle arrest and the induction of apoptosis in MCF-7 cells together with inhibition of tubulin polymerization were demonstrated. Immunofluorescence studies confirmed that compound 22b targeted tubulin in MCF-7 cells, while computational docking studies predicted binding conformations for 22b in the colchicine binding site of tubulin. Compound 22b also selectively inhibited aromatase. Conclusions: Based on the results obtained, these novel compounds are suitable candidates for further investigation as antiproliferative microtubule-targeting agents for breast cancer.